2013
DOI: 10.1371/journal.pone.0070499
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus (MRSA) Is Increasing in Norway: A Time Series Analysis of Reported MRSA and Methicillin-Sensitive S. aureus Cases, 1997–2010

Abstract: BackgroundAccurate estimates of the incidence and prevalence of methicillin-resistant Staphylococcus aureus (MRSA) infections are needed to inform public health policies. In Norway, where both MRSA infection and carriage are notifiable conditions, the reported incidence of MRSA is slowly increasing. However, the proportion of MRSA in relation to all S. aureus isolates is unknown, making it difficult to determine if the rising incidence is real or an artifact of an increasing number of tests performed.AimTo cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 24 publications
0
24
0
2
Order By: Relevance
“…However, community acquired MRSA (CA-MRSA) has become endemic in the US and is now the most common cause of soft tissue infection in the emergency room in many countries 1215. The prevalence of CA-MRSA is higher in the US when compared to Europe but the prevalence in Europe is rising 1621…”
Section: Risk Factorsmentioning
confidence: 99%
“…However, community acquired MRSA (CA-MRSA) has become endemic in the US and is now the most common cause of soft tissue infection in the emergency room in many countries 1215. The prevalence of CA-MRSA is higher in the US when compared to Europe but the prevalence in Europe is rising 1621…”
Section: Risk Factorsmentioning
confidence: 99%
“…The increase in clinical MRSA infections supports the latter. In a Norwegian study, a time series analysis revealed an actual increase in MRSA incidence irrespective of the screening policies or the amount of S. aureus findings [21].…”
Section: Discussionmentioning
confidence: 98%
“…Their resistance is determined by receptors encoded by mecA gene located on the bacterial chromosome which is an element of staphylococcal cassette chromosome mec. Acquiring resistance by S. aureus strains is associated with spreading of staphylococcal cassette chromosome mec included in the so-called genomic islands [27]. …”
Section: Introductionmentioning
confidence: 99%